ROLE OF MUSEUMS OF UZBEKISTAN IN THE LIFE OF SOCIETY (early 20th century) (Scientific journal of the Fergana State University, 2024)
This article discusses the role of museums in public life, their activities and the development of museum affairs. As you know, museums play an important role in broadening one’s horizons and intellectual enrichment. At the beginning of the 20th century, the activities of museums were not given due attention. Which consequently led to the fact that museums were insufficiently visited sites. The question was about promoting the museum business, organizing and expanding new exhibitions, developing human resources, and attracting the attention of the population. Further efforts and resources were concentrated on resolving this issue.